Removal of escherichia coli using waste stabilization pond: A simulation in climatic conditions of Libya - Faskol Adel; Racoviţeanu Gabriel (E3S Web of Conferences, 2019)
The most important determinant when recycling of wastewater for agriculture is that related to public health. This paper investigates the removal of Escherichia Coli/coliform in the waste stabilization pond as simulation as assessing of mitigating health risk. A case study in climatic conditions of Libya. As a result of a computer program based waste stabilization pond design based on parameter uncertainty and 10,000-trial Monte Carlo simulations, were developed for a series of anaerobic, facultative and maturation ponds to produce on a 95%-ile value <1000 E. Coli per 100 ml. While a number of influent of E. Coli bacteria was (156.732×106 E. Coli /100ml). Where it decreased was a number of the effluent (10 E. Coli /100ml). Where the efficiency of removal E. Coli bacteria was (99.999 %). And the overall hydraulic retention time it took 89.548 days in the anaerobic pond, facultative pond, first maturation pond and twelve of the subsequent maturation ponds. To satisfy practice 2006 WHO guidelines for the safe use of wastewater in agriculture.